Immunoregulation of microglia with tocotrienols - Tan, Shi Wei (2012)
Microglia, the ‘brain macrophages’, are the only immune cells in the central nervous system (CNS). Activated microglia are responsible for inflammatory responses and have been noted in the pathophysiology of various neurodegenerative diseases. Continuous activation of microglia resulting in chronic neuroinflammation is thought to exacerbate neuronal damage. Therefore, modulating the inflammatory responses of microglia may be the key to limiting or treating inflammatory events that occur within the CNS parenchyma. Vitamin E is well-known for its anti-inflammatory and its anti-oxidative properties. Natural vitamin E consists of eight chemically distinct compounds: α -, β - ,γ - and δ-tocopherol; α -, β - ,γ - and δ-tocotrienol. Interestingly, tocotrienols has shown better neuroprotective ability than tocopherols. However, to date, there is no approach in studying anti-inflammatory effects of tocotrienols on microglia responses. This study was to elucidate the possible regulatory function of tocotrienols on microglia. First, palm α -,γ - and δ-tocotrienol fragments and Tocomin 50% (a tocopherol/ tocotrienol complex) were screened for their ability to reduce nitric oxide (NO) production by BV2 microglia (an immortalized cell line). BV2 cells were treated with tocotrienols at various concentrations (100 nM, 250 nM, 2.5 µM, 10 µM and 50 µM) for 24 hrs and stimulated with 1 µg/mL lipopolysaccharide (LPS). Highest concentration of all 4 tocotrienols fragments limited NO production by LPS-stimulated BV2 cells without affecting their cell viability, as determined by the MTS assay. Among the tocotrienols fragments tested, δ-tocotrienol reduced the NO production most by approximately 50% after 48 hrs of LPS stimulation (p<.05). Hence, δ-tocotrienol (3.96 µg/mL (10 µM) and 19.80 µg/mL (50 µM)) and Tocomin 50% (47.50 µg/mL and 237.50 µg/mL) were chosen for downstream experiments, by investigating their effects on i-NOS gene expression, proliferation and CD40 surface marker expression in BV2 cells. δ-tocotrienol was found not inhibiting i-NOS mRNA expression to the extent that was expected based on its ability to limit NO production by BV2 cells. Tocomin 50% on the other hand significantly inhibits i-NOS gene expression by 51% (p<.05), indicating that the 2 forms of vitamin E have distinct mechanisms for their ability to reduce NO. Utilising the tritiated thymidine proliferation assay, pre-treating BV2 cells with δ-tocotrienol was found to promote proliferation of both resting and LPS-stimulated microglia. On the other hand, when LPS-treated BV2 cells were post-treated with δ-tocotrienol, cells’ proliferation rate was found not being affected. Apart from that, with flow cytometric immunophenotyping, both δ-tocotrienol and Tocomin 50% were discovered to reduce CD40 activation marker expression levels. 237.50 µg/mL of Tocomin 50% showed highest reduction on CD40 expression in LPS-stimulated BV2 cells by 32%. The findings from this project suggest a potential role for tocotrienols to limit the inflammatory activities of microglia within the CNS and thus may offer a potential therapeutic agent for neurodegenerative and neuroinflammatory diseases.